Impact of physical seismic damage on the fire resistance of reinforced concrete walls. (10th September 2018) - Ni, Shuna; Birely, Anna C.
Highlights: Investigated the effect of physical earthquake damage on fire resistance of RC walls. Walls with non-uniform reinforcement exhibit a complex deformation history. Seismic damage reduces both the thermal-insulation and load-bearing fire resistances. Insulation criterion controls the fire resistance of earthquake-damaged walls. The lateral restraint to walls mitigates the negative effect of earthquake damage. Abstract: Numerical simulations are conducted to investigate the impact of physical seismic damage on the fire resistance of (steel) reinforced concrete (RC) structural walls. A wall with characteristics representative of typical construction in seismic regions is utilized as the basis of the simulations. A two-story wall is considered, with lateral restraint at all floors and at the top only to simulate loss of restraint from floor slabs. The behavior of an undamaged wall is assessed relative to the behavior of slices of walls typically explored in simulation studies. The non-uniform layout of reinforcement is shown to provide a complex deformed shape. Individual damage states, representative of damage observed following earthquakes and in laboratory tests, are introduced to the wall to assess impact on fire resistance. Cracking is shown to have a greater impact on the thermal-insulation fire resistance than on the load-bearing fire resistance. Cover loss or core concrete crushing in the boundary elements or web is shown to result in the possibility of increased out-of-plane deformations and decreased fire resistance. The location of cover loss has remarkable impact on the deformed shape of a wall and its load-bearing fire resistance. Lateral restraint at the floors provides significant support that minimizes the effects of damage on the load-bearing fire resistance. While the load-bearing fire resistance is reduced by damage in the wall studied, fire resistance times are not of concern; however additional studies would be warranted for thin walls and walls with large axial load ratios.